Association between sex hormone-binding globulin and kidney function in men: results from the SPECT-China study. Issue 17 (5th September 2022) - Zhang, Haojie; Chen, Chi; Zhang, Xuan; Wang, Yuying; Wan, Heng; Chen, Yi; Zhang, Wen; Xia, Fangzhen; Lu, Yingli; Wang, Ningjian
Abstract: Background: The association between sex hormone-binding globulin (SHBG) and renal function has rarely been reported in men. We aimed to investigate the above association in a community-based Chinese population. Methods: A total of 5027 men were included from the survey on prevalence for metabolic diseases and risk factors, which is a population-based study conducted from 2014 to 2016 in Eastern China. The estimated glomerular filtration rate (eGFR) was calculated according to the chronic kidney disease Epidemiology Collaboration equation. Low eGFR was defined as eGFR <60 mL·min −1 ·1.73 m −2 . Results: After adjusting for age, smoking, metabolic factors, and testosterone, through increasing quartiles of SHBG, a significantly positive association between SHBG quartiles and eGFR was detected in men (Q1 vs. Q4, β −2.53, 95% confidence interval −3.89, −1.17, P trend < 0.001). Compared with the highest quartile of SHBG, SHBG in the lowest quartile was associated with 96% higher odds of low eGFR (odds ratio 1.96, 95% confidence interval 1.10, 3.48) in the model after full adjustment. According to the stratified analyses, the associations between a 1-standard deviation increase in serum SHBG and the prevalence of low eGFR were significant in men aged ≥60 years old, waist circumference <90 cm, diabetes (no), hypertension (yes), dyslipidemia (no), and nonalcoholic fatty liver disease (no). Conclusions: Lower serum SHBG levels were significantly associated with lower eGFR and a higher prevalence of low eGFR in Chinese men independent of demographics, lifestyle, metabolic-related risk factors, and testosterone. Large prospective cohort and basic mechanistic studies are warranted in the future.